2017
DOI: 10.1007/978-3-319-51409-3_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heat Shock Factors in Mammalian Spermatogenesis

Abstract: Heat shock transcription factors (HSFs), as regulators of heat shock proteins (HSPs) expression, are well known for their cytoprotective functions during cellular stress. They also play important yet less recognized roles in gametogenesis. All HSF family members are expressed during mammalian spermatogenesis, mainly in spermatocytes and round spermatids which are characterized by extensive chromatin remodeling. Different HSFs could cooperate to maintain proper spermatogenesis. Cooperation of HSF1 and HSF2 is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 94 publications
0
36
0
Order By: Relevance
“…In addition to genes that synthesize nutrients necessary for anther and microspore development, we found that Hsfs and Hsps were differentially expressed under different fertility conditions (different environmental temperatures during the wheat growing season), and thus we speculated that they may be related to anther development [37]. The Hsfs on the sex chromosomes of humans and animals have been shown to affect spermatogenesis [38,39]. Coincidentally, in recent years, the HSFs involved in male reproductive cell protection have also attracted attention in plants.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to genes that synthesize nutrients necessary for anther and microspore development, we found that Hsfs and Hsps were differentially expressed under different fertility conditions (different environmental temperatures during the wheat growing season), and thus we speculated that they may be related to anther development [37]. The Hsfs on the sex chromosomes of humans and animals have been shown to affect spermatogenesis [38,39]. Coincidentally, in recent years, the HSFs involved in male reproductive cell protection have also attracted attention in plants.…”
Section: Introductionmentioning
confidence: 93%
“…Spermatogenesis is an intricate developmental process that depends on proper SSC maintenance to allow for the continuous production of sperm (de Rooij, 2017). In most mammals, testes are located in the scrotum outside the body, which allows spermatogenesis to occur at optimal temperatures substantially lower (4-5 °C) than the core body temperature (Widlak and Vydra, 2017). Spermatogenesis is highly thermo-sensitive such that elevated testicular temperature results in germ cell apoptosis, compromised sperm quality, and increased risk for infertility (Reid et al, 1981;Rockett et al, 2001;Yin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether such a mechanism might allow for the transmission of potentially damaged genetic material. Interestingly, it has been reported that heat stress does not induce pro-survival pathways via activation of heat shock transcription factors (HSFs) in meiotic and post-meiotic cells germ cells; rather, these cells undergo apoptosis, presumably to mitigate such unfavorable outcomes (Kus-Liskiewicz et al, 2013;Widlak and Vydra, 2017). Therefore, it is conceivable that the elevated heat stress threshold of SSC allows these select cells to survive and restore spermatogenesis, thereby preventing permanent azoospermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During initiation of the HSR, global gene transcription and protein synthesis are halted, presumably to diminish the level of misfolded proteins in the cell, whereas the expression of stress-responsive genes is increased due to selective activation of some transcription factors, i.e., Heat Shock transcription Factors (HSFs). In mammals, the HSF family includes several members (HSF1, HSF2, HSF3, HSF4, and loosely related HSF5, HSFX and HSFY), which differ in their pattern of expression and differently affect the expression of stressresponsive genes [4,5].…”
Section: Introductionmentioning
confidence: 99%